The making of Northeast Asia - Calder, Kent E. (Studies in Asian security., 2010)
This book offers a detailed analysis of the domestic politics of regionalism in the three major nations of Northeast Asia (China, Japan, and Korea), as well as in the most important external actor, the United States.